THE WALAGARA MARRIAGE RITUAL: The Negotiation between Islamic Law and Custom in Tengger (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
A dialectic between Islamic law and local custom has been the main feature of Islam in Indonesia. As it is elsewhere, the interplay between local custom of Hindu Tengger society in East Java with Islamic law as ethic-norm of Islam cannot be avoided in the framework of negotiation between the two entities. This article seeks to answer how Tengger marriage ritual of Walagara as the local culture apply to Muslim minority in the region and how Islam as legal norm for Muslims adapts the local custom. This result of the study shows that is Tengger society there has been negotiation and compromise in the application of marriage ritual in Walagara ritual. This ritual is understood symbolically as a tradition that should be preserved and applied by adherents of all religions in the region, which necessitates paradigmatic shift in Tengger society toward the existence of Walagara from a religious ritual to become a mere tradition. Marriage is solemnized based on religion of the bride and groom, hence Walagara ritual is observed. In this regard, the negotiation between Islamic law and local custom is symbolic-substantive which creates a hybrid ritual combining both entities.